Technical Features of Biventricular Repair for Unbalanced Transitional AVSD With LVOTO. Issue 6 (November 2021) - Kiraly, Laszlo; Shah, Nishant Ch; Duke, Christopher
Surgical management of left ventricle outflow tract obstruction in infants with right-dominant unbalanced transitional atrioventricular septal defect poses difficulties. A two-month-old infant with transitional atrioventricular septal defect and complex left ventricle outflow tract obstruction presented in cardiogenic shock. The patient underwent successful biventricular repair. The operative procedure included detachment of the anterior bridging leaflet and resection of its chordal attachments. Septal myectomy was performed with creation of an interventricular communication, followed by patch augmentation of the left ventricular outflow tract and anterior bridging leaflet. The zone of apposition between anterior and posterior bridging leaflets was closed. The repair resulted in effective augmentation of the left ventricular inflow and outflow tracts.